Development of a self-administered questionnaire to identify levers and barriers to adherence to medication regimens for chronic disease: The QUILAM project - Audrey Lehmann; Carine Meslot; Matthieu Roustit; Jean-Didier Bardet; Aurélie Gauchet; Benoît Allenet (PLoS ONE, 2025)
Objective We aimed to develop a generic questionnaire for use in routine clinical practice to identify barriers and levers to medication adherence, particularly for patients with chronic disease, in order to implement targeted interventions. Materials and methods To generate items we conducted a narrative literature review and qualitatively analyzed semi-structured interviews of patients with chronic diseases (type 2 diabetes, chronic obstructive pulmonary disease and heart failure). Items were classified according to the five dimensions that influence medication adherence proposed by the WHO. Qualitative reduction of the number of items was conducted by a panel of experts. This long questionnaire was tested on ambulatory patients and analysis of responses enabled quantitative item reduction. Validation of the short questionnaire and stability over time was tested on an independent cohort of patients, and again 15 days later. Results The 194 items extracted from the literature review (validated in several pathologies) and/or from analysis of 45 interviews, spanned all five dimensions of medication adherence according to the WHO. The expert panel reduced the number of items to 62. The analysis of responses from 112 patients using factorial component analysis reduced the final questionnaire to 14 questions each scored on a 7-point Likert-type scale. A validated visual analogue scale (0–100) was added to evaluate medication adherence in general. The final version was well accepted by patients and took 5–10 minutes to complete, with little missing data. In an independent community pharmacy population (n = 55) concordance of the results between day 0 and day 15 was acceptable. Conclusion This generic questionnaire (initially developed in French) for the identification of barriers and levers to medication adherence in patients with chronic disease could help care teams to structure and propose help-with-adherence visits to their patients and personalize interventions to improve patient outcomes.